Supply Chain Risk Management on Health Outcomes: the Role of Information Technology Capability - Ofori , Issah; Yeboah, Hanson Obiri; Agboyi, Rosemary Makafui; Baah, Samuel Agyei; Asare, Charles (Journal of Marketing Studies, 2025)
Purpose: Most studies on supply chain risk management (SCRM) and health outcomes have focused on developed countries, leaving a gap in understanding how these dynamics play out in developing nations. This study seeks to address the gap by conducting the moderating effect of information technology capability on the relationship between supply chain risk management and health outcomes. Methodology: The research adopts a positivist philosophy. The study employs an explanatory research design, which aims to determine the cause-and-effect relationships between the variables.. The population of the study comprises individuals and organizations directly involved in the supply chain and healthcare sectors. A stratified sampling technique is employed to ensure representation from various subgroups within the population, such as supply chain managers, IT specialists, and healthcare workers. Using a confidence level of 95% and a margin of error of 5%, the sample size is calculated to be 220 participants. The study utilizes primary data sources. Findings: There is a strong and significant positive relationship between supply chain risk management and health outcomes. There is a significant and strong positive relationship between Information Technology Capability and Health outcomes. There is a positive and significant moderating role of Information technology capability in the relationship between supply chain risk management and health outcomes. Unique contribution to theory, practice and policy: Healthcare organizations can leverage big data analytics, artificial intelligence (AI), and blockchain to proactively identify and mitigate supply chain risks, leading to better patient care and resource allocation. Governments and health regulators can use IT-powered risk management frameworks to enforce standardized protocols for healthcare logistics, improving equity and accessibility. The study recommends that healthcare organizations should prioritize investment in robust IT infrastructure to ensure their supply chains are equipped to handle dynamic risks effectively. Organizations should also integrate IT into their existing supply chain risk management frameworks. Health care organizations must prioritize the collection, analysis, and utilization of data to enhance decision-making in the supply chain.